Analysis of Climate and Soil Variables as Determinant Factors for Internal Quality of Tawangmangu Citrus - YAYAN APRIYANA; . HARYONO; . SUCIANTINI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
In Tawangmangu, citrus (Citrus nobilis L.) has a specific taste which may be affected by biophysical characteristics such as soil and climate. Yet, the nature of this citrus in relation with biophysical characteristics is rarely studied. The present study was aimed to (1) identify variables of soil and climate that affect the quality of citrus, and (2) characterize the quality of citrus spatially and temporally. The study was conducted covering deskstudy, field survey and laboratory analysis. Climate and soil parameters were ascertained by identifying citrus and its production, characterizing the farmer practices, observing selected climate and soil parameters, and formulating the selected climate and soil parameters in every stage of citrus growth. The quality of citrus product was ascertained throughlaboratory and organoleptic analysis. The results showed that citrus has better internal quality under the topography of more than 1,000 m above sea level (asl) and the average rainfall of 3,166 mm year-1, on Acrudoxin Hapludands soils compared with that growing in area of lower than 1,000 m asl and the average rainfall of 2,715 mm year-1 on Typic Dystrudepts soils. Citrus of Tawangmangu with good quality of yield needs low temperatureabout 190C and radiation about 320 kal cm-2 in flowering season while high and stable temperature of 22-230C and radiation about 400 kal cm-2 are needed during maturing period until fruiting period. Total Dissolved Solid and acid values significantly affected by most of macro nutrient i.e. N, P, K and micro nutrient i.e. Fe, B, and Cu, and also sand mineral i.e. opaque, volcanic glass and labradorit under the topography of more than 1,000 m asl. Meanwhile in area of lower than 1,000 m asl, total solublesolidity significantly affected by CEC, Al, organic matter, micro nutrient and also Opaque, Volcanic Glass and Labradorit. Acid value significantly affected by macro nutrient. Sweets content significantly affected by Hornblende, Augit, and Hiperstin. Therefore, citrus of Tawangmangu can be more adaptable if planted in Typic Dystrudepts on area of more than 1,000 m asl.